Effects of Tractor Speed and Tillage Patterns on Soil Properties and Bush Density Under Semi-Arid Conditions in the Rabia Region - Mohsin, Yahya y (American Journal of Botany and Bioengineering, 2025)
This field experiment was conducted in the semi-arid region of Rabia, Northwest Iraq, during the 2024 growing season to evaluate the interactive effects of tractor speed and tillage patterns on soil physical properties and weed density. A split-split plot design under a randomized complete block layout (RCBD) with three replications was employed, where tractor speed (4.5 km/h vs. 3.0 km/h) was assigned to the main plots, tillage frequency (once vs. twice) to sub-plots, and leveling practices plus weed management to sub-sub plots. The results revealed that employing a tractor speed of 4.5 km/h with twice tillage significantly improved soil moisture content (16.8%) and porosity (52.6%), compared to the lower speed and single tillage which recorded 13.5% and 48.9%, respectively. This mechanical enhancement directly reduced weed dry weight to 32.5 g.m⁻² in the optimal treatment, while the highest weed biomass (290.0 g.m⁻²) was observed under low speed and single tillage. Furthermore, tomato plants exhibited superior performance under high speed and repeated tillage, achieving maximum plant height (86.3 cm), branching (4.9 branches/plant), and total soluble solids (5.8% TSS), whereas the lowest values were recorded at 75.0 cm, 3.8 branches, and 5.1% TSS, respectively. Economically, this combination yielded the highest net profit (3250 USD.ha⁻¹), contrasting sharply with the minimum profit (1900 USD.ha⁻¹) under reduced tillage and speed. These findings underscore the pivotal role of optimizing tractor operational parameters and tillage regimes in enhancing soil structure, suppressing weeds, and ultimately improving tomato yield quality and profitability under semi-arid conditions.